(NmORIS rAWELX I EGO TWOR^ESTWOs - (NsMIRNOW w(B.(Nw(B.s ((NlENINGRADs (NmUZYKAs, 1981)
(Nw KNIGE O^ER^ENY LI^NOSTX I TWOR^ESWO FRANCUZSKOGO KOMPOZITORA(B. (NKOTORYE AWTOR RASSMATRIWAET W SWQZI S OB[ESTWENNO(B-(NISTORI^ESKOJ OBSTANOWKOJ I HUDOVESTWENNYMI TE^ENIQMI \POHI(B.s
Keywords: (NmONOGRAFIQs